The Impact of Unilateral Experimental Rat Varicocele Model on Testicular Histopathology, Leydig Cell Counts, and Intratesticular Testosterone Levels of Both Testes - (:unkn) unknown (UROL & NEPHROL RES CTR-UNRC, 2013)
Purpose: Varicocele, most treatable pathologic condition in male infertility, exerts unfavorable effects on testicular ultrastructure via various mechanisms. In this study we aimed to demonstrate adverse effects of varicocele on both testes. Materials and Methods: Twenty one adult male Albino rats were divided into 3 groups. Sham operation was performed for group 1 (control group), and this group of rats were sacrificed 4 weeks later. Experimental varicocele model was performed for group 2 (varicocele group) and these animals were sacrificed 4 weeks after the operation. In group 3 the rats were varicocelectomized 4 weeks later. This group of rats were sacrificed at 4 weeks postoperatively. The level of testicular damage was examined, and serum testosterone and intratesticular testosterone levels were measured. Results: Mean (+/- SD) damage scores of the right testes of the sham, varicocele, and varicocelectomy groups were 0, 1.64 +/- 1.3, and 1.21 +/- 0.3, respectively. There was no statistically significant differences between damage scores of groups 2, and 3 (P =.320), relevant scores of both groups were determined to be significantly higher than group 1 (P =.009, and P =.001). Mean (+/-) damage scores of the left testes of the three groups were detected to be 0.43 +/- 1.13, 2.29 +/- 1.15, and 1.78 +/- 0.39, respectively. The difference between varicocele, and varicocelectomy groups was not statically significant (P =.112). Conclusion: Unilateral varicocele has deleterious effects on both testes. There was no statistically significant difference as for histopathologic recovery following varicocelectomy.
Keywords: varicocele; rats; testis; parhology; spermatogenesis; animals; SPERM CONCENTRATION; MALE-INFERTILITY; BLOOD-FLOW; TEMPERATURE; APOPTOSIS; REPAIR; MEN